In silico determination of novel SARS-CoV-2 envelope protein ion channel inhibitors - Nina Kobe; Lennart Dreisewerd; Matic Pavlin; Polona Kogovšek; Črtomir Podlipnik; Uroš Grošelj; Miha Lukšič (Computational and Structural Biotechnology Journal)
The SARS-CoV-2 envelope protein (2-EPRO), a viroporin crucial for viral pathogenesis, is a promising target for antiviral drug development as it is highly conserved and functionally important. Although it is a promising therapeutic target for the treatment of COVID-19, it has often been overlooked in previous studies. In this study, a high-throughput virtual screening of nearly one billion compounds was performed, followed by rigorous filtering and re-docking. Eight best-scoring and chemically versatile lead candidates were identified. In molecular dynamics simulations, three of these ligands showed stable protein-ligand complexes occupying the 2-EPRO channel pore. Among these, ZINC001799167680 (L3) and ZINC001081252239 (L2) exhibited the strongest binding affinity, with key interactions at residues ASN15, THR11 and GLU8 identified by Molecular Mechanics Poisson-Boltzmann Surface Area analysis. All ligands were compared with the known inhibitor rimantadine and showed stronger binding to the protein. These in silico results highlight the potential of focusing on the 2-EPRO ion channel in the development of novel COVID-19 therapeutics and pave the way for further in vitro and in vivo studies.